Effects of insulin glargine U300 versus insulin degludec U100 on glycemic variability, hypoglycemia, and diet evaluated by continuous glucose monitoring in type 1 diabetes: a retrospective cross‐sectional study - Pin‐Lun Tsai; Chia‐Hung Lin; Yu‐Yao Huang; Hsin‐Yun Chen; Yi‐Hsuan Lin (Kaohsiung Journal of Medical Sciences)
Abstract The impacts of insulin degludec U100 (Deg‐100) and insulin glargine U300 (Gla‐300) on glycemic variability (GV) in patients with type 1 diabetes, as well as the impact of major nutrient components on GV in these patients, remain unclear. This was an observational, cross‐sectional, retrospective study. Type 1 diabetes mellitus patients treated with either Deg‐100 or Gla‐300 as basal insulin were enrolled. After the participants underwent continuous glucose monitoring, GV indices and major nutrient components were analyzed. Forty patients with type 1 diabetes were enrolled, and 20 participants used Deg‐100, and 20 used Gla‐300. There was no significant difference in major nutrient components between the two groups. Better GV indices of standard deviation, coefficient of variation, mean amplitude of glycemic excursion, AUCn, M‐value, CONGA1, CONGA2, and CONGA4 were noted in the Gla‐300 group versus Deg‐100 group. Compared with patients who received once‐daily injection in the morning (QD), Deg‐100 administration once daily at bedtime (HS) yielded a higher low blood glucose index during both day and nocturnal periods, indicating a higher risk of hypoglycemic events. By contrast, there were significantly lower levels of CONGA1, CONGA2, and CONGA4 during insulin Gla‐300 QD administration than during HS administration, indicating a lower GV of a short interval. In this real‐world study involving type 1 diabetes patients, Gla‐300 appears to offer more stable glucose variability than Deg‐100. Administering once‐daily injections could lower the risk of hypoglycemia in the Deg‐100 group and minimize GV in the Gla‐300 group compared to bedtime injections.